Bone health in advanced prostate cancer: pathophysiology and management strategies - Rana R McKay; Heather Hofflich; Gina Woods; Richard Andres; Azeez Farooki (The Oncologist, 2026)
Abstract Bone loss and bone metastases can increase morbidity and impair quality of life for patients with prostate cancer. Use of hormonal agents can compromise bone integrity from treatment initiation, and the emergence of bone metastases further increases the risk of symptomatic skeletal-related events. Management of bone health should therefore be pivotal across the prostate cancer continuum. Current guidelines recommend that all men starting or receiving androgen-deprivation therapy for prostate cancer be assessed regularly for bone loss using predictive tools such as dual-energy X-ray absorptiometry and Trabecular Bone Score. Bone health agents (BHAs) are recommended for all men with castration-resistant prostate cancer with skeletal metastases to prevent symptomatic skeletal-related events, and for high-risk men receiving androgen-deprivation therapy to prevent treatment-related bone loss. Options include bisphosphonates such as zoledronic acid and alendronate, and the receptor activator of nuclear factor kappa-B ligand inhibitor denosumab. Patients should be monitored for adverse effects of BHAs, such as osteonecrosis of the jaw and hypocalcemia. Alongside BHAs, there are treatment options for metastatic castration-resistant prostate cancer associated with beneficial bone-related effects, notably abiraterone acetate, enzalutamide, and radium-223. In this narrative review, we focus on how bone health management can be integrated into standard clinical practice in men with advanced prostate cancer. We also present a test-and-treatment algorithm for bone health management in men with metastatic prostate cancer. Improving treatment-related bone loss and proactively managing bone metastases should be standard practice in all men with prostate cancer to improve health outcomes and quality of life.